(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article presents materials for the effective use of secondary material resources and industrial waste of the textile, clothing and knitwear industries, the production of nonwoven glued materials, thermal insulation materials using effective equipment and technology, polymer materials and binders, as well as use in various industries.